2008
DOI: 10.1080/17482960701726123
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes of the lower cervical spinal cord under neutral and fully flexed position by MRI in Chinese patients with Hirayama's disease

Abstract: We examined MR images of the spinal cord from the neutral neck to the fully flexed neck position in Chinese patients with Hirayama's disease (HD). MRI was performed on 25 HD patients and 31 healthy controls in the neutral and fully flexed neck positions. The mean anterior-posterior diameter (APD) and transverse diameter (TD) of the cervical cord at C6 level in the different positions was measured. Localized lower cervical cord atrophy and asymmetric cord flattening in a neutral neck position were highly sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Some authors (31,33,34) reported the presence of forward shifting of the dural sac in all their patients. Nevertheless this sign is not always present in HD patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Some authors (31,33,34) reported the presence of forward shifting of the dural sac in all their patients. Nevertheless this sign is not always present in HD patients.…”
Section: Discussionmentioning
confidence: 95%
“…Two of our patients (25%) showed T2 hyperintensities of the spinal cord respectively at C5-C6 and C6-C7 levels. High signal alterations on T2 weighted images without cord compression are described in the literature, but this finding is inconstant, presenting in about one third or less of the patients (10,27,34,42).…”
Section: Discussionmentioning
confidence: 96%
“…The disease affects mainly young males and after progressing for a few years it generally stabilizes and remains confined to the upper limbs (1). In many cases HD is associated with lower cervical cord atrophy and asymmetric cord flattening (2, 3). Concerning its etiology, some authors suggested mechanical compression of the lower cervical spine during flexion, but this pathogenic mechanism is not unanimously accepted (15).…”
Section: Introductionmentioning
confidence: 99%
“…The disease affects mainly young males and after progressing for a few years it generally stabilizes and remains confined to the upper limbs (1). In many cases HD is associated with lower cervical cord atrophy and asymmetric cord flattening (2,3). Concerning its etiology, some authors suggested mechanical compression of the lower cervical spine during flexion, but this pathogenic mechanism is not unanimously accepted (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases HD is associated with lower cervical cord atrophy and asymmetric cord flattening (2,3). Concerning its etiology, some authors suggested mechanical compression of the lower cervical spine during flexion, but this pathogenic mechanism is not unanimously accepted (1)(2)(3)(4)(5). Others consider HD as a segmental form of spinal muscular atrophy (6).…”
Section: Introductionmentioning
confidence: 99%